تحديد القطاعات الرائدة في الاقتصاد السوري باستخدام روابط الجذب الأمامية الكلية - حيدر, عز الدين; يوسف, حسين (Latakia University Journal - Economic and Legal Sciences Series, 2018)
In this study, we examined the input and output tables of the Syrian economy during the period 2006-2013. We calculated the direct frontal attraction links of the economic sectors during the considered period to determine the leading economic sectors in the Syrian economy. The best sector is construction sector with an average value of 2.08 That the investment of one lira in the construction sector will generate an added value of 1.08 pounds This sector has maintained a value of more than 2 in most years of the studied period. We also note existence a group of sectors that can be described as leading economic sectors Because of high value front links, such as paper and its products, printing, extractive industries, water and electricity, wood industry, and Spinning industry, while the smallest value of total front in financial, insurance and real estate sectors was only 1.15. We also found a statistically significant relationship between each of the leading sectors and the rest of these sectors. يهدف هذا البحث بدراسة جداول المدخلات والمخرجات الخاصة بالاقتصاد السوري خلال الفترة بين 2006 و2013 ومن ثم قمنا بحساب الروابط الأمامية المباشرة للقطاعات الاقتصادية خلال الفترة المدروسة لتحديد القطاعات الاقتصادية الرائدة في الاقتصاد السوري. تم التوصل إلى عدة نتائج أهمها أن أفضل القطاعات الاقتصادية كان قطاع البناء والتشييد بمتوسط قيمة 2.08 بمعنى أن استثمار ليرة واحدة في قطاع البناء والتشييد سيقوم بتوليد قيمة مضافة قدرها 1.08 ليرة, حيث حافظ هذا القطاع على قيمة تفوق 2 في أغلب سنوات الفترة المدروسة كما لاحظنا وجود مجموعة من القطاعات يمكن وصفها بأنها قطاعات اقتصادية ريادية لتحقيقها قيمة مرتفعة من حيث الروابط الأمامية الكلية وهي: الورق ومنتجاته والطباعة, و الصناعات الإستخراجية, و الماء والكهرباء, و صناعة الخشب والموبيليا والأثاث, وصناعة الغزل بينما كانت أقل قيمة للروابط الأمامية الكلية لدى قطاع المال والتامين والعقارات ب 1.15 فقط. كما وجدنا أثر ذو دلالة إحصائية بين كل قطاع من القطاعات الريادية وبين باقي هذه القطاعات.